Examining men’s disclosures, influences, and motivations for seeking mental health treatment - Stanfield, Matthew Hunter (Kansas State University, 2019)
Numerous studies note that women are more likely than men to seek out therapy. It is suggested that the differences in mental health utilization rates between genders are a function of gender socialization towards general help-seeking behaviors as well as about attitudes towards mental health. Central to understanding men’s mental health help-seeking behavior are factors of stigma, social support, motivations for therapy, and basic psychological needs. This study examined the relationship of these factors on men’s mental health-seeking behaviors by utilizing the frameworks of social influence theory and self-determination theory. A total of 317 adult males residing within the United States responded to items relating to disclosure, social influence, and motivations for therapy. Men also read and responded to a series of short stories and measures about disclosure, influence, and seeking therapy. A latent profile analysis was first conducted to determine the distinct number of profiles of men on the observed variables of stigma, social support, motivations for therapy, and basic psychological needs. From the latent profile analysis, a total of four distinct profiles emerged: Reluctant, Open, Restrictive, and Considering. Analyses were then conducted to determine the differences between these profiles on psychological openness, intentions to seek therapy, self-compassion, shame, and adherence to traditional masculine norms. The differences between these profiles were also examined using a multinomial logistic regression relating to men’s disclosure to seek therapy and the influence of a partner, parent, close friend, religious or spiritual leader, and medical doctor to seek therapy. A final multinomial logistic regression was conducted to analyze the differences amongst these profiles on their reported importance to seek therapy for depression and anxiety, substance use, and suicidality. These findings demonstrate important implications for those working with men in therapy, for public education efforts surrounding men’s mental health, and for those in relationships to men who are experiencing a mental health-related issue. Specifically, recognizing the heterogeneity of men’s help-seeking behavior on stigma, social support, motivations for therapy, and basic psychological needs can allow therapists to better work with men in therapy in addition to increasing the knowledge of men’s mental health issues to those in relationships with men.
Keywords: Men; Help-seeking behavior; Mental health stigma; Self-determination theory; Social influence theory; Therapy